Kids detector system via radio frequency identification (RFID): article / Mohammad Aizat Noor Azman - Noor Azman, Mohammad Aizat (2009)
This paper will discuss about how to create a system or device that can help teacher or caretaker in monitoring their kids at the kindergarten using the RFID technology. The system is operates by warn the caretaker in term of sound if their kids over the area/ boundries of the antenna. Visual Basic. Net was used to process the data and show the output. Finally the strength of the RF wave was measured to determine how far the antenna of the system can transmit signal and to determine if there is any different when the tag is at different locations.